2011
DOI: 10.1007/s10531-011-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries and trade of seahorses in Brazil: historical perspective, current trends, and future directions

Abstract: Seahorses (Hippocampus spp.) are globally threatened by overexploitation and habitat destruction; they are also regarded as susceptible to heavy exploitation due to some of their life-history traits. From an economic perspective, they are fishes with high monetary value and marketability. Seahorses are now listed in Appendix II of CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora), to ensure that the international trade is not detrimental to the survival of wild populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 32 publications
0
69
0
6
Order By: Relevance
“…This is because populations pressed by aquarium harvesting activities had shown lower densities and smaller individuals (Ibama 2007(Ibama , 2008a. However, the effectiveness of such measure is questionable since untrained and ill-intentioned dealers used to mislabel specimens of either H. erectus or H. reidi as they were Hippocampus kuda Bleeker, 1852(Monteiro-Neto et al 2003, while field surveys demonstrated that only H. reidi was actually exported, and the given quota could be doubled if 250 H. reidi were traded under the name of H. erectus (Rosa et al 2011). Furthermore, there is still controversy about the distribution and taxonomy of Brazilian seahorses.…”
Section: Holocentrus Adscensionismentioning
confidence: 99%
“…This is because populations pressed by aquarium harvesting activities had shown lower densities and smaller individuals (Ibama 2007(Ibama , 2008a. However, the effectiveness of such measure is questionable since untrained and ill-intentioned dealers used to mislabel specimens of either H. erectus or H. reidi as they were Hippocampus kuda Bleeker, 1852(Monteiro-Neto et al 2003, while field surveys demonstrated that only H. reidi was actually exported, and the given quota could be doubled if 250 H. reidi were traded under the name of H. erectus (Rosa et al 2011). Furthermore, there is still controversy about the distribution and taxonomy of Brazilian seahorses.…”
Section: Holocentrus Adscensionismentioning
confidence: 99%
“…En Brasil, H. erectus generalmente se captura como fauna acompañante en las pesquerías del camarón blanco Litopenaeus schmitt, reforzando el criterio de que es más frecuente a mayor profundidad, aunque también se ha encontrado en aguas poco profundas en la costa sur, a pocos metros de la superficie, asociados a macroalgas y briozoos para su anclaje (Rosa et al 2011). En este estudio, la especie se registró entre 1 y 2 m de profundidad, es posible que el método de muestreo utilizado sea la causa de la poca cantidad observada de individuos.…”
Section: Discussionunclassified
“…Al solo aparecer en tres meses, no se pudo determinar la época reproductiva para la especie H. erectus, a diferencia de Teixeira & Musick (2001) que reportan picos reproductivos de mayo a octubre y Rosa et al (2011) los registraron de enero a marzo.…”
Section: Discussionunclassified
See 2 more Smart Citations